Analisis Kuat Tarik dan Umur Perekat Poliamida Berbasis Gelatin dan Asam Adipat dengan Variasi Jumlah Minyak Sawit sebagai Pemlastis - Santosa, Alvin Rizani Ardiansyah; Zain, Anisya Salsabiela; Pancasakti, Bima Prasetya; Budhijanto (Jurnal Teknik Kimia USU, 2022)
The adhesive that is widely used today is the synthetic one, which is carcinogenic to humans. It is necessary to produce adhesives based on natural resources (bioadhesive) to reduce the use of synthetic adhesive. Gelatin is a compound that has amine groups, while adipic acid is an organic acid that has carboxylic groups in its chemical structure so they can be primary ingredients to make adhesive. The research objective is to reduce the use of synthetic adhesives with best quality of bioadhesive. The steps of making the adhesives included polymerization reaction and hydrolyzed palm oil addition. The polymerization reaction is carried out in batches at 90 â„ƒ and 1 atm with mole ratio palm oil to gelatin variety of 0; 0.04; 0.08; 0.17; 0.33; 0.5; and 1. The best result for tensile strength is the ratio of 0.33 mole ratio of palm oil to gelatin for 1 day, 3 days, 7 days, and 14 days of curing time, respectively 1575.71 kPa, 2197.30 kPa, 3387.31 kPa, dan 3708.23 kPa.